2004
DOI: 10.1099/vir.0.80118-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation among human adenoviruses: genome sequence and annotation of human adenovirus serotype 1

Abstract: The 36 001 base pair DNA sequence of human adenovirus serotype 1 (HAdV-1) has been determined, using a 'leveraged primer sequencing strategy' to generate high quality sequences economically. This annotated genome (GenBank AF534906) confirms anticipated similarity to closely related species C (formerly subgroup), human adenoviruses HAdV-2 and-5, and near identity with earlier reports of sequences representing parts of the HAdV-1 genome. A first round of HAdV-1 sequence data acquisition used PCR amplification an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…Through sequence analysis, it has been demonstrated that the genomes of all human adenoviruses have similar genetic organization (11,24,26).…”
mentioning
confidence: 99%
“…Through sequence analysis, it has been demonstrated that the genomes of all human adenoviruses have similar genetic organization (11,24,26).…”
mentioning
confidence: 99%
“…Standard PCR methodologies were used to amplify regions to be sequenced, as detailed for HAdV-1 (31). PCR conditions, in brief, called for Pfu Ultra DNA Polymerase (Stratagene, Inc.) at 2.5 units in a total volume of 50 l containing 5 l of 10ϫ polymerase buffer (Stratagene, Inc.), 3.5 l dimethyl sulfoxide (7% final), deoxynucleoside triphosphates (200 M; stock solutions of 1 mM), oligonucleotide primers (0.5 M; stock solutions of 10 M), and template DNA (30 ng; stock solutions of 33.16 ng/l).…”
mentioning
confidence: 99%
“…The genome sequence of HAdV-4, determined earlier by the Epidemic Outbreaks Consortium (39), was used to generate a scaffold of minimally tiled and overlapping primers for PCR amplification and DNA sequencing, leading to threefold coverage of each base with complementary reads of the strands. As shown in a study to rapidly resequence the HAdV-1 genome, this strategy allows efficient resequencing of related genomes at minimal cost and effort (31). PCR was performed using Pfu Ultra DNA Polymerase (Stratagene, Inc.) and 30 ng of purified adenoviral DNA as a template.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence was identified as originating from HAdV-1 later, when the full genomic sequence of HAdV-1 was published (Lauer et al, 2004). Subsequently, the presence of HAdV-1 was confirmed in cats in Japan (Phan et al, 2006) and Brazil as well (Luiz et al, 2010), but no other reports on sequencelevel identification of AdVs in felid hosts have been published to date.…”
mentioning
confidence: 99%